Hiérarchies urbaines en Amérique portugaise : São Paulo, Recife, Vila Rica - xvie-xviiie siècle (Les élites) - Laura de Mello e Souza (Mélanges de la Casa de Velázquez, 2023)
The first urban centers in Portuguese America date back to the 16th century, but urbanization was rarefied throughout the colonial period. In an extremely varied territory, it is possible to highlight three distinct experiences, which emerged in specific contexts and gave rise to very different societies: São Paulo, whose population turned to the hinterland in search of indigenous hands for their crops (16th century); Recife, a merchant village created during the Dutch occupation of the northeast (17th century); Vila Rica, seat of the gold region that attracted thousands of adventurers (18th century). Peculiar experiences that attest to the variety assumed by urban forms in this sub-continent.